2020
DOI: 10.1557/adv.2020.85
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of Bendable Cubic NiO and In2O3 Thin Films on Synthetic Mica for p- and n-type Wide-Bandgap Semiconductor Oxides

Abstract: AbstractBendable p-type NiO and n-type In2O3 thin films were epitaxially grown on synthetic mica using mist chemical vapor deposition. It was found that at a growth temperature of 400 °C, epitaxially grown cubic (111) NiO thin films developed twin rotational domains, and the epitaxial relationship between each domain and the substrate was (111) NiO [1-10] or [10-1] || (001) synthetic mica [100]. In the visible light region, the epitaxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Although the {204} reflection of mica is two-fold symmetric, the three observed peaks with a 120° interval for the mica substrate show a pseudo-three-fold symmetry. 45,46 This pseudo-three-fold symmetry is previously ascribed to three rotated structures with similar plane spacing and distribution. 45 In the upper half of Fig.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Although the {204} reflection of mica is two-fold symmetric, the three observed peaks with a 120° interval for the mica substrate show a pseudo-three-fold symmetry. 45,46 This pseudo-three-fold symmetry is previously ascribed to three rotated structures with similar plane spacing and distribution. 45 In the upper half of Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Considering that the rocksalt structures exhibit three-fold symmetry, the six-fold peaks observed in the {200} reflections of the Fe:GeTe are attributed to an in-plane twin domain structure. 46 The diffraction peaks of the {200} Fe:GeTe reflection were observed at the same positions as those of the {204} mica reflection, indicating that the Fe:GeTe thin film was grown along the in-plane direction of the mica substrate. A schematic of an epitaxial Fe:GeTe/mica film with the determined orientation relationship, (111) Fe:GeTe 8(001) mica and h1% 10i Fe:GeTe 8[100] mica , is constructed and presented in Fig.…”
Section: Structural and Compositional Analysis Of Fe:gete/mica Epilayersmentioning
confidence: 85%
“…ITO and ZnO:B are both n-type wide-bandgap semiconductors that not only form heterojunctions with the Sb 2 Se 3 layer but also serve as growth substrates for the Sb 2 Se 3 layer. [60,61] The properties of growth substrates determine the growth direction of (Sb 4 Se 6 ) n ribbons. [62] The growth direction of the (Sb 4 Se 6 ) n ribbons affects the carrier transport characteristics, thus influencing device performance.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
“…Although 2D materials have no dangling bonds at the cleavage surface, epitaxial thin films are grown by van der Waals epitaxy. Heteroepitaxial growth of various oxide thin films, such as VO 2 , MoO 2 , ZnO, , NiO, In 2 O 3 , Al-doped ZnO (AZO), ε-Fe 2 O 3 , and κ-Ga 2 O 3 , on muscovite mica and synthetic mica has been previously demonstrated. Furthermore, it has been shown that inducing bending stress in epitaxial thin films grown by van der Waals epitaxy changes the resistivity of ZnO and the magnetic anisotropy of ε-Fe 2 O 3 . , …”
Section: Introductionmentioning
confidence: 99%
“…Mist chemical vapor deposition (CVD) was utilized to grow epitaxial VO 2 thin films on flexible synthetic mica. In previous studies, we have demonstrated van der Waals epitaxy of various oxides, such as ZnO, NiO, In 2 O 3 , and κ-Ga 2 O 3 , by mist CVD. In addition, VO 2 thin films grown on rigid quartz substrates by mist CVD had high visible transmittance and exhibited large changes in the infrared transmittance with MIT .…”
Section: Introductionmentioning
confidence: 99%